Climate Cognition Crisis: Urgent Call to Address Air Pollution and Extreme Heat Impacts in Learning Environments of Children in South and Southeast Asia - Sahni, Pooja Swami; Dewan, Surat; Sachdeva, Manya; Ranathunga, Nayomi; Fadhullah, Widad; Abdullah, Jafri Malin; Roy, Tusar; Pal, Bidhan; Baloch, Shoukat; Adhikari, Bikash; Ikiz, Burcin; Mishra, Jyoti (Malaysian Journal of Medical Sciences, 2025)
The climate crisis combined with air pollution is increasingly disrupting the foundational conditions for healthy cognitive development and learning, particularly among children in vulnerable regions. In South and Southeast Asia, escalating levels of air pollution and extreme heat are synergistically threatening the neurocognitive health, educational attainment, and long-term potential of millions of children. Many schools in the region lack adequate ventilation, cooling infrastructure, and environmental monitoring, leaving children vulnerable to both acute and chronic health impacts. The review explores the effects of air pollution and extreme heat on cognitive function, behaviour, and academic performance in children. It highlights the urgent need to prioritise children’s brain health in climate adaptation, education, and public health agendas. Beyond outlining the problem, the article identifies critical gaps and opportunities for action. It stresses the need for real-time, child-centred data as a missing link for informed decision-making. The lack of public awareness and a compelling narrative around the climate cognition link is also examined as a driver of inaction. Finally, the article offers a science-driven blueprint for change, outlining a path forward that integrates neuroscience, environmental monitoring, education reform, and equity-focused policy. Understanding and responding to this “climate cognition crisis” is not only a public health and developmental imperative, but also central to building resilient, future-ready societies in South and Southeast Asia.